Análisis y propuesta de un reglamento de admisión y empleo, de funciones y valuación de puestos para la empresa Román Hermanos Cia. Ltda., de la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, Para el año 2017 - Calero Bustamante, Eva Genoveva (2017)
The main objective of this research work is to analyze and propose a regulation on admission and employment, functions and job valuing for the company Román Hermanos Cía. Ltda., From the city of Nueva Loja, Canton Lago Agrio, province of Sucumbíos, for the year 2017, in such a way that by incorporating within the organic structure the human talent management tools proposed in the present investigation will facilitate the company perform the proper management of the staff. For the realization of this study it was necessary to apply methods such as deductive, inductive and synthetic. As well as research techniques such as direct observation, surveys and interview. The direct observation made it possible to verify the management and development of the company's work activities. The interview was applied to the General Manager, Mr. Roberth Román Bajaña. In addition, surveys were applied to 54 internal clients. In the results section, the situational diagnosis of the company is shown, as well as the information of the surveys applied to the internal clients, through statistical tables with their respective analysis and interpretation. In the discussion, the proposal of the regulation of admission and employment, and the manual of functions for the company Román Hermanos Cía. Ltda., Which.